1994
DOI: 10.1111/j.1365-2249.1994.tb06109.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the chemokine superfamily in rheumatoid arthritis

Abstract: The infiltration of leucocytes into the joint of rheumatoid arthritis (RA) is believed to be mediated by chemotactic factors released by activated cells. In this study, examination was made of the gene expression and production of the chemokine superfamily in RA patients by reverse transcriptase-polymerase chain reaction (RT-PCR) and immunoprecipitation. Cultured synovial fibroblasts were found capable of expressing and producing IL-8, GRO, monocyte chemotactic and activating factor (MCAF), macrophage inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
42
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(43 citation statements)
references
References 31 publications
0
42
0
1
Order By: Relevance
“…Recently, it has become clear that cells such as fibroblasts, which were thought to be relatively inert structural components of the tissue, actually play important roles in regulating tissue homeostasis in health and disease. Synovial tissue and synovial fluid from RA patients contain increased concentrations of several chemokines produced by resident synoviocytes and infiltrating cells alike (53)(54)(55). At the level of chemokine production, the potential of different chemokines to be induced (or repressed) with differing kinetics may be one mechanism involved in controlling the magnitude, time dependency, and phenotype of specific leukocyte subsets recruited to sites of inflammation (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has become clear that cells such as fibroblasts, which were thought to be relatively inert structural components of the tissue, actually play important roles in regulating tissue homeostasis in health and disease. Synovial tissue and synovial fluid from RA patients contain increased concentrations of several chemokines produced by resident synoviocytes and infiltrating cells alike (53)(54)(55). At the level of chemokine production, the potential of different chemokines to be induced (or repressed) with differing kinetics may be one mechanism involved in controlling the magnitude, time dependency, and phenotype of specific leukocyte subsets recruited to sites of inflammation (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…In double-blind, placebo-controlled studies, patients treated with IFN␥ showed significantly improved morning stiffness, grip strength, swelling of an index joint, and erythrocyte sedimentation rate (54)(55)(56)(57)(58). More recently, however, in a multicenter, randomized, doubleblind trial of 197 patients with active RA, IFN␥ was found to be well tolerated but proved to be no more effective than placebo (59).…”
Section: Discussionmentioning
confidence: 99%
“…In this disease, proinflammatory chemokines are thought to play a pivotal role in the attraction of leukocytes to sites of inflammation leading to the initiation, maintenance, and progression of the inflammatory process (20,21). Indeed, a number of CC chemokines, including CCL5, CCL2, CCL3 and CCL4, are present at elevated levels in the joints of arthritic patients (22)(23)(24)(25) as well as in animal models of this disease (26,27). These levels coincide with the recruitment of, for example, CCR5 + monocytes and T cells into human synovial tissues (28).…”
mentioning
confidence: 99%
“…The CC chemokines, MCP-1/CCL2 and RANTES/CCL5, which are chemotactic for monocytes and T lymphocytes (2)(3)(4), are detected in rheumatoid arthritis synovial fluid (5,6). Rheumatoid arthritis synovial tissue (ST) 3 fibroblasts produce RANTES and MCP-1 upon stimulation with TNF-␣ and IL-1␤, mediators critical for the pathogenesis of rheumatoid arthritis (5,(7)(8)(9). Cells positive for RANTES and MCP-1 and their corresponding receptors are present in rheumatoid arthritis ST and colocalize with CD68 ϩ macrophages (10).…”
mentioning
confidence: 99%